STUDENTS PERCEPTIONS TOWARDS THE EFFECTIVE FEEDBACK PRACTICES IN THE LARGE EFL WRITING CLASS BASED ON STUDENTS ENGLISH PROFICIENCY LEVEL - Susanti, Rini (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
Motivated by my own experience in teaching and learning academic writing in a large class of more than 50 students, I aim to find out the students perceptions towards the effective feedback practices in a large EFL writing class in Indonesia. There were 150 students participating by answering the the questionnaire. The data was analyzed based on English proficiency level (the students TOEFL scores). The findings showed that based on the students English proficiency level, they perceived feedback from their lecturers is effective when it is given in written form, while from their peers, it should be in oral form.